Reconstruction of English Test on 2nd Grade Students at SMP Negeri 2 Konawe Selatan - Etriyanti, Etriyanti; Hanna, Hanna; Kamaluddin, Kamaluddin (Universitas Halu Oleo, 2021)
This research was accomplished to investigated the quality of previous English teacher-made test and showed which aspect was reconstruct of the English teacher-made test on the second grade at SMP Negeri 2 Konawe Selatan. The design of this research was qualitative by applaying MER (Model of Educational Reconstruction) approach, which contained (1) Content structure analysis, (2) Empirical study, (3) Reconstruction process. The data analysis used qualitative analysis to see the apperances of each item test that consisted of 50 items multiple choice. There were criteria of face validity, they were; (1) appropriatness of grammar, (2) the clarity and unambiguity of items, (3) the correct spelling of words, (4) the corret structuring the sentences, (5) the correct punctuation and lowercase/uppercase letters, and (6) the used of constractions. In other word, the qualitative analysis needed to get to know which aspect has reconstruct.The result of qualitative analysis in face validity level revealed that quality of the test in term of face validity there were 24 items question (48%) categorized have face validity and there were 26 items question (52%) categorized mismacth with the criteria of face validity. Thereby, 26 items question did not match with the criteria of face validity. Thus, the items question need to reconstrct to make the improvement of quality to each items question to match with the criteria of face validity.